Early vasodilator treatment in myocardial infarction: appropriate for the majority or minority?. Issue 10 (October 1992) - Hargreaves, A D; Kolettis, T; Jacob, A J; Flint, L L; Turnbull, L W; Muir, A L; Boon, N A
Abstract : Objective —To assess the influence of vasodilator treatment started early after myocardial infarction on left ventricular size and function. Setting —Coronary care unit, Royal Infirmary, Edinburgh. Patients —105 patients with acute myocardial infarction (systolic blood pressure >90 mm Hg) were randomised within 24 hours of the start of pain. Unlike previous studies 88% of the patients received thrombolysis. Methods —Double blind randomised placebo controlled study with either 12·5 mg of captopril three times daily or 20 mg of isosorbide mononitrate three times daily for 28 days. Main outcome measures —Clinical outcome and left ventricular size and function assessed by echocardiography, radionuclide ventriculography, and magnetic resonance imaging. Results —There was no difference in left ventricular size or function in either treatment group as measured one week after the end of the trial. Even the placebo group tended to decrease left ventricular diameter over the four week study period (one week: 5·0 (0·1) ν, five weeks: 4·8 (0·1) cm, NS). Four patients had an adverse clinical outcome in the placebo group whereas no adverse outcome was seen in the captopril group. Conclusions —Vasodilator treatment may be of limited value or of no benefit for most infarct patients, particularly those treated with thrombolytic agents. Captopril, however, may benefit patients at high risk.